Instrumentation for measurement and characterization of mixed-signal devices - Ribeiro, Diogo Carlos Alcobia (2018)
This PhD thesis work is about the development of radio frequency oriented measurement and characterization approaches for mixed-signal devices. Mixed-signal devices are an important building block for newer, higher data-rate and smart radios. However, intuitive and simple characterization approaches have not yet been developed. The most basic mixed-signal device is an ADC or a DAC. The ADCs and DACs will be considered in this work, as well as, more complex mixed-signal devices and even entire (integrated) radio front-ends. A microwave network analysis approach, in an S-parameters like fashion, will be used to augment the modeling techniques of mixed-signal devices. This type of behavioral modeling approach is extensively supported within the tools used during the RF design stages. This will allow RF engineers to account for the non-ideal eﬀects of these devices in a simpler way. The ﬁnal outcome may be used to establish an instrument capable to characterize both basic and more complex mixed-signal devices, in the same way a traditional VNA does for fully analog devices.